Severe Rh alloimmunization and hemolytic disease of the fetus managed with plasmapheresis, intravenous immunoglobulin and intrauterine transfusion: A case report. Issue 3 (December 2015) - Houston, Brett L.; Govia, Rachelle; Abou-Setta, Ahmed M.; Reid, Gregory J.; Hadfield, Marie; Menard, Chantalle; Noyd, Jocelyn; Main, Susan; Zarychanski, Ryan
Abstract: Rh alloimmunization remains a potentially devastating complication of pregnancy, with fetal anemia causing hydrops and intrauterine death. Intrauterine transfusion is the standard treatment, but is particularly dangerous before 20 weeks gestation. When the need for intrauterine transfusion is anticipated early in pregnancy, immune-modulating therapies such as plasmapheresis and IVIG have been used to delay transfusion to a later gestational age. We report a 35-year-old G5P1 Rh(D)-negative woman with severe Rh alloimmunization managed successfully with sequential plasmapheresis, intravenous immune globulin and intrauterine transfusion. The optimal plasmapheresis treatment protocol and incremental benefit of IVIG remains unknown.